Teachers and Parents' Perceptions of Care for Students with Type 1 Diabetes Mellitus and Their Needs in the School Setting - Laura Armas Junco; María Fernández-Hawrylak (MDPI AG, 2022)
The high incidence of Type 1 Diabetes Mellitus (DM1) increases the likelihood of teachers having students with this illness in their classrooms. The objective of this study is to investigate the needs of students with DM1 during the school day from the perspective of both teachers and parents. A mixed methods study was designed and a questionnaire was administered to practicing teachers in Pre-primary Education, Primary Education, Compulsory Secondary Education, and Further Education, as well as Vocational Education within both the province and the city of Burgos (Castile and Leon, Spain) who may have students with DM1. Semi-structured interviews were also conducted with mothers and fathers, members of the Burgos Diabetics Association (ASDIBUR). In the questionnaires administered to the teaching staff, 54.8% affirmed that they knew of students with DM1 at their centers. Of those questioned, 51.2% affirmed that they knew of the existence of action protocols on DM, and 45.2% declared that they had received specialized information on the illness; 92.8% believed that there was no discrimination at their center towards students with DM, and 82.8% thought that the educational center raised no objections to students with DM departing on trips during the school year. In their interviews, both family and teachers assessed the material and human resources as insufficient and called for the presence of school nurses at the educational centers. It is important to raise the awareness of the educational community about the needs of students with DM1 and to provide guidelines on emergency situations to teachers and staff at the centers.